Virtual audiology education tools: A survey of faculty, graduate students, and undergraduate students - Svec, Adam; Morgan, Shae D (The Journal of the Acoustical Society of America, 2022)
Due to global shifts at educational institutions from in-person courses to online formats caused by the COVID-19 pandemic, the current study aimed to estimate whether currently available virtual audiology education tools are helpful for acquiring necessary audiology skills and knowledge from the perspective of both educators and students. Therefore, a remote survey was developed and distributed to faculty and students in undergraduate communication sciences disorders and graduate audiology programs. Although participation was somewhat limited, the trends observed in the survey results suggested that the majority of both educators and students found the subset of virtual tools easy to use, that these tools improved teaching methods and learning outcomes, and that these tools would likely be used again.